2009
DOI: 10.1038/sj.bjc.6605461
|View full text |Cite
|
Sign up to set email alerts
|

Clinical presentation and initial management of Black men and White men with prostate cancer in the United Kingdom: the PROCESS cohort study

Abstract: BACKGROUND: In the United States, Black men have a higher risk of prostate cancer and worse survival than do White men, but it is unclear whether this is because of differences in diagnosis and management. We re-examined these differences in the United Kingdom, where health care is free and unlikely to vary by socioeconomic status. METHODS: This study is a population-based retrospective cohort study of men diagnosed with prostate cancer with data on ethnicity, prognostic factors, and clinical care. A Delphi p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
25
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 16 publications
3
25
0
1
Order By: Relevance
“…This evidence is consistent with reports of comparable biological disease characteristics in blacks and whites. 23,24 Our results also support the premise that differences in outcomes based on race are reduced or eliminated when patients have access to similar opportunities for treatment. Thus, race may be a marker for other prognostic factors.…”
Section: Discussionsupporting
confidence: 77%
“…This evidence is consistent with reports of comparable biological disease characteristics in blacks and whites. 23,24 Our results also support the premise that differences in outcomes based on race are reduced or eliminated when patients have access to similar opportunities for treatment. Thus, race may be a marker for other prognostic factors.…”
Section: Discussionsupporting
confidence: 77%
“…The authors concluded that prostate cancer grows more rapidly and/or shows early transformation from latent to aggressive disease in African-American men compared with white men. This observation is consistent with studies from the UK, France, and South Africa, which all reported that black men presented with prostate cancer at a younger age than white men [28][29][30] .…”
supporting
confidence: 93%
“…5 These population-based observations indicate that although SES and access to therapy undoubtedly explain some of the racial disparities in prostate cancer prognosis, there may be important tumor characteristics that differ in white and African American patients with prostate cancer. These findings are not limited to the United States and were confirmed in other countries including Great Britain, 6,7 France, 8 and Brazil. 9 However, it is also important to keep in mind that a large hospital-based cohort study in the United Kingdom found that after fully controlling for treatment and stage, race was no longer a predictor of survival or treatment outcomes.…”
supporting
confidence: 67%